Stoicheia tou Kosmou : Interpretatie van een Nieuwtestamentische term - Cramer, A.W., (European History and Culture - Book Archive pre-2000., 1961)
With an English summary. On the interpretation of the Greek words 'Stoicheia tou kosmou' ('Powers of the cosmos') as used by St. Paul.